PENGARUH KONSENTRASI EKSTRAK DAUN TEMBAKAU SEBAGAI INHIBITOR PADA TULANGAN BETON BERTULANG - Sultan, Mufti Amir; Barmawi, Nurtalia; Abbas, Muhammad Yunus Hi (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2021)
Reinforced concrete structures that are destroyed due to corrosion attacks need serious handling. One method of preventing corrosion is by using an inhibitor. In this study, the inhibitors used were tobacco leaf extract inhibitors with variations of 0%, 4% and 8%. The method used to analyze the corrosion rate that occurs is the weight loss method. Tests carried out by providing electricity to the test object using a voltage of 5V. The results showed that the influence of the addition of tobacco extract inhibitors at concentrations of 4% and 8% was able to reduce the density of anodic and cathodic currents which resulted in a reduced corrosion rate in steel reinforcement. This proves that tobacco extract can be used as a green corrosion inhibitor because it effectively decreases the corrosion rate.